GENDER IN EDUCATION OF VOLUNTEERS - Dončevová, Silvia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The study focuses on the possibilities and importance of eliminating gender inequality and gender stereotypes in the area of voluntary activities in social area. The aim of the study is to show that gender inequality and gender stereotypes have negative impacts on work in volunteering in social sphere, and to show the possibilities of education of trying to improve the current state of the problem. These negative phenomena are manifested especially in the behaviour towards clients, in communication and solving critical situations. The study brings results of our own research in this area.